Nuda i jej typologie - Chruszczewski, Michał H. (Kultura-Społeczeństwo-Edukacja, 2020)
Boredom is a very interesting issue that persists in our contemporary day and age. It is not easy to define it in a positive sense (by listing its properties, which constitute a presence of something, rather than a lack of something), as it has vastly differentiated causes and symptoms. The paper presents a variety of types of boredom identified from various points of view in the humanities and social sciences. According to the author, two of these typologies are particularly convincing. The first introduces the division into the state and a trait of boredom, while the latter – describing only the state of boredom in terms of arousal and affect – postulates the existence of neutral, calibrating, searching, reactant and apathetic boredom. These typologies have been juxtaposed with others, with their similarities and differences identified and indicated.